Distant neighbours. Economic adjustment processes at the Finnish-Russian border - Heikki Eskelinen; Kimmo Niiranen (European Regional Science Association (ERSA), 2002)
For decades, the closed East/West border was an effective barrier for cross-border interaction at a local and regional level. It was reflected, among other things, in production structures and settlement patterns in the border regions. Since around 1990, economic and other forms of cross-border linkages have been possible, and they have raised the issue about adjustment processes, that is, whether regional and local economic actors are able to utilise existing complementarities and create new ones, and how this will make itself felt in the roles of the border regions in the international division of labour. The paper investigates regional adjustment processes in the case of the Finnish-Russian border, which is characterised by one of the deepest socio-economic and cultural gaps in Europe. First, the reasons for the specialisation of the neighbouring regional economies under the period of the closed border are analysed. Against this background, the repercussions of the partial opening of the border are evaluated in relation to the other driving forces of their development trends in the 1990s. It is concluded that the regions on both sides have lagged behind their respective national averages, although border-related adjustment processes have had quite diverse economic impacts. In Finland, these impacts have remained relatively marginal in most border regions. In the Russian borderlands, some local and regional economies have undergone profound changes in their market orientation due to the proximity of the border; instead of being specialised producers for the Russian market, they are now locked in the international division of labour as economic peripheries.
Keywords: 330